Overdiagnosis of atypical lipomatous tumors/well-differentiated liposarcomas by morphological diagnosis using only HE stained specimens: a case–control study with MDM2/CDK4 immunostaining and MDM2/CDK4 fluorescence in situ hybridization - Kentaro Nomura; Masato Tomita; Kishio Kuroda; Masakazu Souda; Ko Chiba; Akihiko Yonekura; Makoto Osaki (BMC Cancer)
Abstract Background Lipomatous tumors represent the most common type of soft tissue neoplasms. Mouse double minute 2 homolog (MDM2)/cyclin-dependent kinase 4 (CDK4) immunostaining is considered effective in differentiating between benign lipomas and intermediate malignant atypical lipomatous tumors/well-differentiated liposarcomas (ALT/WDLPSs). However, these tumors have traditionally been diagnosed histopathologically using hematoxylin and eosin-stained specimens, which is referred to here as morphological diagnosis. In this study, the accuracy of morphological diagnoses that had been made before MDM2/CDK4 immunostaining became available for distinguishing between lipoma and ALT/WDLPS was examined. Methods The study participants were 109 patients with a morphological diagnosis of lipoma (68 patients) or ALT/WDLPS (41 patients) who had undergone surgical resection of the tumor in our hospital between 2009 and 2012. Tissue samples from all patients were used for MDM2/CDK4 immunostaining and the confirmation of MDM2/CDK4 amplification by fluorescence in situ hybridization (FISH). Results Of the 41 patients with a morphological diagnosis of ALT/WDLPS, only 17 were positive for MDM2 FISH. In addition, one of the 68 patients with a morphological diagnosis of lipoma showed MDM2 amplification by FISH. When the definitive diagnosis of ALT/WDLPS was made by the positive results of MDM2 FISH, the sensitivity and specificity of morphological diagnosis were 41.5% and 98.5%, respectively. The sensitivity of MDM2 and CDK4 immunostaining was 55.6% and 40.0%, respectively, and their specificity was 87.0% and 84.6%, respectively. This indicates that the diagnostic accuracy of these immunostaining assays was not particularly high. The clinical features suggesting ALT/WDLPS were: patient age (older), maximum tumor diameter (large, cut-off value of 125 mm), tumor location (lower limb), and tumor depth (deep-seated). Conclusions Morphological diagnosis alone can accurately diagnose lipomas. However, it has a propensity to overdiagnose ALT/WDLPS. Thus, MDM2 FISH should be used more proactively, not only for lesions with obvious morphological abnormalities, but also for lipomatous tumors that are clinically suggestive of ALT/WDLPS.